Conversational topics of urban Malaysia preschoolers / Evelyn Kow Pei Ping - Kow, Evelyn Pei Ping (2012)
The central aim of this study is to identify the conversational topics of urban Malaysian preschoolers. Using quantitative and qualitative approaches, this descriptive study elicited data from an urban, English medium child care and development centre, which provided two groups that comprised 18 preschoolers of Chinese, Malay, Indian and Punjabi descent. A compact digital camera with video recording function was used to record the preschoolers’ reading time, activity time, drawing time, playtime and mealtime conversations on a first-hand basis for four consecutive days and on two separate occasions – September 2009 and March 2010. These conversations yielded 26 clips totalling four hours, 10 minutes and five seconds, from which a total of 2626 lines of utterances were coded according to the 48 topic categories that make up the referential frames of Time, Person and Content. The overall findings indicate that preschoolers talked primarily about the present (31.6%), non-human subjects (11.6%) and themselves (11.1%), which concurs with the study of Marvin, Beukelman, Brockhaus and Kast (1994). Data showed that the 10 most popular topics of conversation were about the present time, non-human subjects, themselves, their peers, the actions and personal information of themselves and others, being playful, movies/cartoons, descriptions, space and toys. The present study sheds light on the conversational competence of urban Malaysian preschoolers, particularly their selection and elaboration of conversational topics. As this knowledge provides an insight of their linguistic, cognitive, psychological and social development, it is useful in the crafting of a preschool curriculum that is relevant, engaging and stimulating. It may also aid parents, child care professionals, educators in the building and maintenance of their interpersonal relationships with preschoolers. Additionally, it may be used as a yardstick to diagnose difficulties in oral language development among preschoolers and in the devising of a system to assist children with expressive communication disorders.